Macrophage subpopulation identity in Drosophila is modulated by apoptotic cell clearance and related signalling pathways - Brooks, Elliot C.; Zeidler, Martin P.; Ong, Albert C. M.; Evans, Iwan R. (Frontiers in Immunology, 2024)
In Drosophila blood, plasmatocytes of the haemocyte lineage represent the functional equivalent of vertebrate macrophages and have become an established in vivo model with which to study macrophage function and behaviour. However, the use of plasmatocytes as a macrophage model has been limited by a historical perspective that plasmatocytes represent a homogenous population of cells, in contrast to the high levels of heterogeneity of vertebrate macrophages. Recently, a number of groups have reported transcriptomic approaches which suggest the existence of plasmatocyte heterogeneity, while we identified enhancer elements that identify subpopulations of plasmatocytes which exhibit potentially pro-inflammatory behaviours, suggesting conservation of plasmatocyte heterogeneity in Drosophila. These plasmatocyte subpopulations exhibit enhanced responses to wounds and decreased rates of efferocytosis when compared to the overall plasmatocyte population. Interestingly, increasing the phagocytic requirement placed upon plasmatocytes is sufficient to decrease the size of these plasmatocyte subpopulations in the embryo. However, the mechanistic basis for this response was unclear. Here, we examine how plasmatocyte subpopulations are modulated by apoptotic cell clearance (efferocytosis) demands and associated signalling pathways. We show that loss of the phosphatidylserine receptor Simu prevents an increased phagocytic burden from modulating specific subpopulation cells, while blocking other apoptotic cell receptors revealed no such rescue. This suggests that Simu-dependent efferocytosis is specifically involved in determining fate of particular subpopulations. Supportive of our original finding, mutations in amo (the Drosophila homolog of PKD2), a calcium-permeable channel which operates downstream of Simu, phenocopy simu mutants. Furthermore, we show that Amo is involved in the acidification of the apoptotic cell-containing phagosomes, suggesting that this reduction in pH may be associated with macrophage reprogramming. Additionally, our results also identify Ecdysone receptor signalling, a pathway related to control of cell death during developmental transitions, as a controller of plasmatocyte subpopulation identity. Overall, these results identify fundamental pathways involved in the specification of plasmatocyte subpopulations and so further validate Drosophila plasmatocytes as a heterogeneous population of macrophage-like cells within this important developmental and immune model.